UPAYA PENANGGULANGAN ADANYA PELANGGARAN IJIN MENDIRIKAN BANGUNAN DI KABUPATEN BADUNG - Suryana, Kadek Dedy (Jurnal Ilmiah Raad Kertha, 2025)
Permit is a legal instrument from the government that is often used to regulate, discipline and control society, therefore it is easier, simpler compared to laws or regional regulations. However, permits from the government are still based on law, they must not conflict with higher regulations